Construction of NiFeP/CoP nanosheets/nanowires hierarchical array as advanced electrocatalysts for water oxidation. (26th July 2019) - Jiang, Xiaoli; Li, Yao; He, Miao; Zhou, Lingxi; Zheng, Qiaoji; Xie, Fengyu; Jie, Wenjing; Lin, Dunmin
Abstract: Cost-effective hierarchical electrocatalysts with excellent performance and high stability for water splitting play an important role in promoting social sustainable development. Herein, we report a three-dimensional (3D) trimetallic nickel-iron-cobalt phosphide with a hierarchical nanoarray structure grown in situ on carbon cloth via a combined method of two-step hydrothermal reaction and following low-temperature phosphating using a carbon cloth as a conductive substrate. The synthesized NiFeP/CoP/CC exhibits excellent oxygen evolution reaction (OER) catalytic performance, giving small overpotentials of 250 mV, 270 mV and 320 mV at current densities of 20 mA cm −2, 50 mA cm −2 and 200 mA cm −2 in alkaline electrolyte, respectively, with a small Tafel slope of 51 mV dec −1 . In addition, the catalytic activity of the material remains stable for at least 50 h, and the turnover frequency (TOF) is 0.466 mol O2 s −1 at an over potential of 300 mV. These properties of the material are comparable to those of the noble metal catalyst RuO2 /CC, which may be ascribed to the hierarchical microstructure, good conductivity and desirable synergistic effect among metal ions. Highlights: A composite of NiFeP/CoP hierarchical nanoarray prepared by a facile topological phosphidation method. The resulting NiFeP/CoP exhibits excellent oxygen evolution reaction catalytic performance. Low overpotential 320 mV observed at high current density of 200 mA cm −2 . Tafel slope 51 mV dec −1 and long stability at least 50 h.